Ikhtiyār and Tawakkul in The Story of Prophet Ibrāhīm AS and Their Role for Maintaining Mental Health - Elit Ave Hidayatullah; Sahara Permata; Imamuddin Imamuddin (ZAD Al-Mufassirin, 2025)
The background of this research arises from the need to understand the role of Qur’anic teachings in addressing various psychological challenges in the modern era, such as anxiety, stress, and internal conflicts. The story of Prophet Ibrāhīm AS in the Qur’an, whose life was marked by numerous severe trials, provides a model for understanding the integration of ikhtiyār and tawakkul in the life of a muslim. The approach used is a thematic interpretation, analyzing Qur’anic verses related to the story of Prophet Ibrāhīm AS. The findings show that ikhtiyār and tawakkul in the story of Prophet Ibrāhīm AS represent strong faith and function as mechanisms that support mental health. The study also finds that the values of ikhtiyār and tawakkul are relevant to modern life, particularly in addressing doubts, interpersonal anxiety, inner conflicts, and uncertainty about the future. These challenges can be mitigated through ikhtiyār and tawakkul with sincere intellectual (‘aqlī), physical (jasadī), and spiritual (rūḥī) efforts, thus playing a role in maintaining mental health. It is hoped that the results of this research will enrich the study of Qur’anic interpretation, provide practical guidance for Muslims in facing life’s challenges, and serve as a reference for further research on integrating Islamic values to support mental health.